Preventing accidents from reoccurring due to colour coding transition in Malaysian market: A stakeholder analysis - Jaaffar A.H.; Rajadurai J.; Ab. Shokor S.S.; Ismail Z.; Alwi M.N.R. (Science Publishing Corporation Inc, 2023)
The harmonization of cable colour code for electrical installation with the current international standard is very important for Malaysia to ensure supply cables, reliable quality, and reasonable cable price in the Malaysian market as well increase its cable's export to all countries around the world. As the new cable colour code will associate with the change of the colour of the cored cable (e.g. black cored cable former neutral and later phase and blue cored cable former phase and later neutral), the adjustment may increase risk of electrical accidents due to confusion in cable colour code in wiring process. Therefore, a proper action and implementation plan is crucial in handling the cable colour changeover in the hope to safeguarding the safety of electrical trade workers as well as the general public in Malaysia. By using stakeholder analysis, this study propose the action and implementation plan which aimed zero electrical accidents during the cable colour code changeover in Malaysian market. 2018 Authors.